Configuring Pedagogy and Community Culture for Academic Integrity in Kazakhstani Universities [Paper] - Soltys, Dennis (M. Narikbayev KAZGUU University, Nazarbayev University, 2019)
Traditional compliance policing methods to ensure academic integrity tend relatively to ignore the developmental approach, and to ignore whether learning is actually occurring. Cheating and plagiarism indicate a breakdown in pedagogy, which is better addressed by student development than policing. Notwithstanding, the knowledge economy creates both a need for and opportunity to promote academic integrity within a developmental approach, which emphasizes analytical thought and rewards acquisition of soft skills. Quality assurance can be achieved by means followed in conventional institutional accreditations.
Paper presented at The 4th Annual International Conference on Academic Integrity, May 2019
Keywords: The 4th Annual International Conference on Academic Integrity